A fast and simple method of spectral enhancement - Sajid, M. (Society of Exploration Geophysicists, 2014)
The ability to resolve seismic thin beds is a function of the bed thickness and the frequency content of the seismic data. To achieve high resolution, the seismic data must have broad frequency bandwidth. We developed an algorithm that improved the bandwidth of the seismic data without greatly boosting high-frequency noise. The algorithm employed a set of three cascaded difference operators to boost high frequencies and combined with a simple smoothing operator to boost low frequencies. The output of these operators was balanced and added to the original signal to produce whitened data. The four convolutional operators were quite short, so the algorithm was highly efficient. Synthetic and real data examples demonstrated the effectiveness of this algorithm. Comparison with a conventional whitening algorithm showed the algorithm to be competitive. Â© 2014 Society of Exploration Geophysicists.